Experimental treatment of the prototype of DC motor (Research, Society and Development, 2020)
This work aims to present the results of the analytical and experimental study of a prototype of a DC motor developed experimentally. This motor has the principle of motor action, the repulsive forces between magnets or electromagnets. It had as a fundamental basis for analysis of the forces, field and torque acting on the rotor the laws of the magnetostatic, such as the Law of Ampére and the Law of Biot Savart, as well as concepts related to the principle of operation of a DC motor. For the modeling of the experiment the software SketchUp, a tool that allows the construction of geometric models, physical models and finally, a prototype, allowing a strategic positioning of the coils, rotor and stator, with the main objective of the modeling, to present an experiment with characteristics of an electric motor and that its structure bears similarity with the exemplifications made in didactic books. In the construction of the prototype was used elements of low cost, taking advantage of components of discarded equipment. The results obtained through the analytical studies and experimental tests allow to visualize an adequate functioning of the prototype, allowing without many complications to see several topics covered in the course of physics and engineering, such as magnetic fields generated by coils, magnetic force, torque in a loop, magnetic force in a wire traveled by current, speed of a rotor composed of coils immersed in a magnetic field and dipole moment, in addition to its structure allow to arrive at mathematical results about its operation, using basic principles of electromagnetism.